ANALYSIS OF ABILITY TO WRITE THE ARGUMENTATION OF OBSERVATION RESULTS OF X GRADE STUDENTS OF GRAFIKA GADINGREJO VOCATIONAL SCHOOL - Anggraeni, Leni (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
In writing an argument, a strong understanding is needed to be able to understand the language or the meaning contained in it. Therefore, readers who are going to write arguments must read them carefully in order to present evidence or determine the possibility of expressing an attitude or opinion about something. Seeing the importance of the ability to write arguments, the Indonesian language and literature subjects at SMA / SMK were given writing argumentation sub-topics. The purpose of this study was to determine the students' ability to write arguments. This study only consisted of one variable, namely the ability to write arguments with a population of 51 students. Data analysis was carried out by finding the average percentage per indicator of students' argument writing ability by dividing the acquisition score of each indicator by the maximum score of each indicator. Based on the results of the research data analysis, it can be concluded that the average ability of class X students of SMK Grafika Gadingrejo in writing arguments from the observation results is quite adequate with a value of 65.25%. With the average ability per indicator as follows, the list of opinion topics is developed into arguments with a value of 82%, the ability to formulate an argumentation writing framework with a value of 80%, compile arguments coherently with a value of 74%, using conjunctions. between the sentence value 53%, using words according to Enhanced Spelling (EYD) with a value of 47%, and using words according to word choice (diction) with a value of 52%.